Multicomponent adsorption of hexane isomers in MOFs - Bárcia, Patrick da Silva (2010)
We have performed a set of screening studies for quaternary mixtures of hexane isomers n-hexane (nHEX), 3-methylpentane (3MP), 2,3-dimethylbutane (23DMB) and 2,2-dimethylbutane (22DMB) in two porous rigid MOFs (figure 1). First, the chromium trimesate MIL-100(Cr),1 which possesses mesoporous cages accessible through 5-9 Å microporous windows, and secondly the zirconium terephthalate UiO-66,2 which exhibits a 3D microporous (5-10 Å) pore system. The temperature range 323-423 K and partial pressures up to 30 kPa have been explored. Figures 2(a-b) shows typical multicomponent equimolar experiments. For all experiments, the sorption hierarchy in MIL-100 is: nHEX>>>3MP>23DMB>>22DMB while UiO-66 possesses the opposite 22DMB>23DMB>>>3MP>nHEX. The results show that both MOFs can be effective for this separation. Further studies are now being developed to increase the degree of separation.